A finite element study to determine the occurrence of abfraction and displacement due to various occlusal forces and with different alveolar bone height - Kharidhi Laxman Vandana; Mittal Deepti; Muneer Shaimaa; Karnath Naveen; Desai Rajendra (Wolters Kluwer Medknow Publications, 2016)
Background: Noncarious cervical lesions (NCCLs) are rarely described in the periodontal literature, perhaps because no direct link between NCCLs and periodontal lesions has been demonstrated. Aim: The aim of this study is to determine the stress and displacement produced in the tooth at different bone levels under different occlusal load using finite element model (FEM) study. Materials and Methods: Four FEMs of maxillary incisor were designed consisting of the tooth, pulp, periodontal ligament, and alveolar bone at the various level of bone height (25%, 50%, and 75%). Different occlusal load (5 kg, 15 kg, 24 kg, and 29 kg) at an angle of 50° to the long axis of the tooth was applied on the palatal surface at the level of middle third of the crown. All the models were assumed to be isotropic, linear and elastic, and the analysis was performed on a Pentium IV processor computer using the ANSYS software. Results: The maximum stress in the tooth was seen in the cervical region and to a greater extent at the apex for all models. The maximum tooth displacement for all the occlusal loads applied in this study was at the incisal edge with the minimum tooth displacement at the cervical third of the root which shifted apically with the reduction of alveolar bone support. Conclusion: The cumulative effect of increased stress and displacement at the cervical region of the tooth would result in abfraction as the age advances along with other wasting diseases.